Respuesta :

Answer:

[tex] d = 7 + 3\sqrt{3} [/tex] and

[tex] d = 7 - 3\sqrt{3} [/tex]

Step-by-step explanation:

To solve the equation, [tex] d^2 - 14d - 22 = 0 [/tex], using the quadratic formula,

Recall: quadratic formula = [tex] \frac{-b ± \sqrt{b^2 - 4ac}}{2a} [/tex]

Where,

a = 1

b = -14

c = 22

Plug in your values into the formula and solve:

[tex] \frac{-(-14) ± \sqrt{(-14)^2 - 4(1)(22)}}{2(1)} [/tex]

[tex] \frac{14 ± \sqrt{196 - 88}}{2} [/tex]

[tex] \frac{14 ± \sqrt{108}}{2} [/tex]

[tex] d = \frac{14 + \sqrt{108}}{2} [/tex]

[tex] d = \frac{14 + 6\sqrt{3}}{2} [/tex]

[tex] d = (\frac{2(7 + 3\sqrt{3})}{2} [/tex]

[tex] d = 7 + 3\sqrt{3} [/tex]

And

[tex] d = \frac{14 - \sqrt{108}}{2} [/tex]

[tex] d = \frac{14 - 6\sqrt{3}}{2} [/tex]

[tex] d = (\frac{2(7 - 3\sqrt{3})}{2} [/tex]

[tex] d = 7 - 3\sqrt{3} [/tex]